A importância da municipalização do trânsito: estudo de caso – Pau dos Ferros- RN - Araújo, Bruna Soares de (Universidade Federal Rural do Semi-Árido, 2018)
The Brazilian Traffic Code is governed by Law 9,503, decreed in September 1997, establishing a series of competencies and attributions related to traffic management. Among them, it is worth mentioning the obligation of municipalization of traffic to cities with more than 20,000 inhabitants. However, the number of cities that did not adhere to this system is high. Among these cities, we can mention the municipality of Pau dos Ferros, which is located in the state of Rio Grande do Norte. This city is characterized as a commercial hub by offering services such as education, health and leisure to neighboring cities, favoring the existence of a large flow of vehicles that influence the safety and quality of life of the population. This work has the objective of analyzing the problematic issues of transit and indicate the possibilities of improvement through the implementation of municipalization. For this, a bibliographical study was carried out to base the topic covered and on the process of implementing the municipalization of traffic. The results were obtained based on photographic records that highlighted the conflicts arising from the lack of traffic management and an interview with the city planning secretary to understand the pretensions and actions planned to solve these problems. Through the obtained results, it was verified that there are no indicative of projects or actions for the implementation of the municipalization of traffic and portrayed the existing conflicts that interfere in the mobility and safety of the displacements carried out in the city.
Keywords: Legislação; Conflitos; Gestão do trânsito; ENGENHARIAS::ENGENHARIA CIVIL